Increasing Ploidy Level of Garlic (Allium sativum L.) “Tawangmangu Baru” In-Vitro Using Colchicine - Hailu, Molla Gebreyohannes; Wiendi, Ni Made Armini; Dinarti, Diny (Journal of Tropical Crop Science, 2020)
“Tawangmangu Baru” garlic variety is known to have low productivity. The variety is still highly demanded due to its strong flavour and aroma; however, its production has not yet been able to fulfill the local needs of Central Java due to the small size and limited production area. This study aimed to determine the effect of concentration and time duration of colchicine treatment towards increasing the ploidy level of “Tawangmangu Baru” garlic variety for genetic variability. The experimental design used in this study was a complete randomized design with two factorials and 12 combinations. The first factor was concentration of colchicine, i.e. 0.00, 0.02, 0.04, 0.06, 0.08 and 0.10%, and the second factor was the immersion time, i.e. 24 and 48 hours. The result indicated that, 4.72% callus induction was obtained in BDS + 0.4 mg.L-1 2,4-D + 2.0 mg.L-1 kinetin; and 4.0% callus proliferation were obtained in both BDS + 1.5 mg.L-1 2,4-D + 1.0 mg.L-1 kinetin and MS +1.5 mg.L-1 2,4-D and 1.0 mg.L-1 kinetin. The untreated plantlets showed higher mortality rate compared to the explants with 48 hours colchicine treatment. Higher number of shoots were recorded in 0.1% colchicine at 48 hours and lower shoots in 24 hours, whereas 0.1% colchicine at 24 and 48 hours showed the highest ploidy level of total nuclear DNA analyzed by flow cytometry. The genetic diversity of the “Tawangmangu Baru” garlic was successfully enhanced by colchicine and immersion treatment. Mutant lines with tetraploid and mixoploid plants were obtained. The putative lines obtained at 0.1% colchicine treatment were subcultured to produce new mutants before testing the phenotype. The application of colchicine at 24 and 48 hours treatment improved the genetic potential of “Tawangmangu Baru” garlic variety in vitro. The application of colchicine increased the ploidy level and an increase in ploidy is expected to make the bulb size larger. Larger tuber size will increase the tuber weight, and also the overall garlic productivity and production in the future.